2012
DOI: 10.3892/ol.2012.975
|View full text |Cite
|
Sign up to set email alerts
|

Response-specific progestin resistance in a newly characterized Ishikawa human endometrial cancer subcell line resulting from long-term exposure to medroxyprogesterone acetate

Abstract: Abstract. Progestins, particularly medroxyprogesterone acetate (MPA), have for a long time been used as conservative treatment for young patients with clinical stage I, grade I endometrial carcinoma. However, more than 30% of patients with endometrial adenocarcinoma display resistance to endocrine therapies at the time of presentation and most cancer patients that initially respond to progestin treatment will at some point develop resistance, resulting in tumor progression. The cellular mechanisms underlying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…DHCR24 is the final enzyme of cholesterol synthesis, and cholesterol is the essential precursor for all steroid hormones, include progesterone1334. It has been reported that constant progestin stimulation gave rise to a resistance effect to progestin and reduced the expression of PGR35. Therefore, we speculate that DHCR24 might display negative feedback on the PGR.…”
Section: Discussionmentioning
confidence: 84%
“…DHCR24 is the final enzyme of cholesterol synthesis, and cholesterol is the essential precursor for all steroid hormones, include progesterone1334. It has been reported that constant progestin stimulation gave rise to a resistance effect to progestin and reduced the expression of PGR35. Therefore, we speculate that DHCR24 might display negative feedback on the PGR.…”
Section: Discussionmentioning
confidence: 84%
“…While kaempferol has been described as a partial ER agonist in human breast cancer cells and cervical cells [49,50], multiple studies investigating the estrogenic actions of kaempferol in vivo detected no uterotrophic estrogenic effects [37,60], which is further corroborated in this study. Progestin therapy resistance occurs in some populations of patients with endometrial cancer and endometriosis due to reduced or loss of PR protein expression after prolonged treatment [51,67,68]. Endometrial cancer is the most common gynecological malignancy in the United States and the fifth most common cancer among women in the world [47,53,69].…”
Section: Discussionmentioning
confidence: 99%
“…However, almost a third of these patients eventually developed MPA resistance 8 . There are several mechanisms that underlie the acquired resistance to MPA, such as PR dysregulation 28 , Immune system and in ammatory response 29 and the activation of lipid metabolism 30 . Recently, some studies show that ncRNAs such as miRNAs and long ncRNAs (lncRNAs) also play vital roles in MPA resistance.…”
Section: Discussionmentioning
confidence: 99%